2011
DOI: 10.1111/j.1365-246x.2011.05170.x
|View full text |Cite
|
Sign up to set email alerts
|

Antipodal focusing of seismic waves due to large meteorite impacts on Earth

Abstract: S U M M A R YWe examine focusing of seismic waves at the antipode of large terrestrial meteorite impacts, using the Chicxulub impact as our case study. Numerical simulations are based on a spectralelement method, representing the impact as a Gaussian force in time and space. Simulating the impact as a point source at the surface of a spherically symmetric earth model results in deceptively large peak displacements at the antipode. Earth's ellipticity, lateral heterogeneity and a spatially distributed source li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 32 publications
3
37
0
Order By: Relevance
“…The earlier event of the pairs in Figures 13b–f is right after the 2004 Indian Ocean earthquake (Mw 9.1) on 26 December. A large earthquake can amplify disturbances along antipodal directions at the top of the inner core and near the center of the Earth (Meschede et al, 2011). Thus, we conjure a possible scenario that the small‐scale iron patches in the mushy zone of the inner core near the region beneath Sumatra are disturbed by the waves of the great Sumatra earthquakes, which were sampled by steep incident DF phase at relatively large distances.…”
Section: Discussionmentioning
confidence: 99%
“…The earlier event of the pairs in Figures 13b–f is right after the 2004 Indian Ocean earthquake (Mw 9.1) on 26 December. A large earthquake can amplify disturbances along antipodal directions at the top of the inner core and near the center of the Earth (Meschede et al, 2011). Thus, we conjure a possible scenario that the small‐scale iron patches in the mushy zone of the inner core near the region beneath Sumatra are disturbed by the waves of the great Sumatra earthquakes, which were sampled by steep incident DF phase at relatively large distances.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that seismic stresses can be enhanced at the antipode to large impacts, which can result in increased damage formation (e.g., Schultz and Gault, 1975;Asphaug et al, 1996;Schultz and Crawford, 2011;Meschede et al, 2011). Numerical studies by Asphaug et al (1996) and Benz and Asphaug (1994) reveal that the grooves (troughs) in Pola Regio, a region of the asteroid Ida, and the grooves on Phobos may have formed by large impacts (Fujiwara and Asada, 1983;Asphaug and Melosh, 1993).…”
Section: Vesta From Dawnmentioning
confidence: 96%
“…and references therein) based on biostratigraphy, magnetostratigraphy, sedimentology and geochemistry of numerous sequences in NE Mexico and Texas Meschede et al (2011). investigated the global seismic effects of the Chicxulub impact and found that the shock waves would have to be bundled to their greatest effect at the precise opposite side of the planet, the antipode.…”
mentioning
confidence: 99%